The ladder leaning against the wall forms a right angled triangle with the gound and the wall. So we can use the formula:
a² + b² = c²
The ladder is the hypotenuse c²
The vertical leg is b²
The base or horizontal leg is a²
We need to find the length of the base a², so:
a² = c² - b²
a² = 5² - 4²
a² = 25 - 16
a² = 9
a = √9
a = 3
Therefore the bottom of the ladder must be 3 feet from the wall.
F. A line
G. A ray
H. An angle
J. A point
K. A line segment
Answer:
F. A line
Step-by-step explanation:
A line separates a plane into three parts the line and two half-planes.
Looking for an explanation on how to solve these two problems and what the correct answers are. How do I solve these ?
4n-2n=4
-12=2+5v+2v
A general cosine function has the form:
f(x) = A*cos(c + x)
We want to find the value of A that matches the one in the image, and we will find that A = 3
Ok, a general cosine function is:
f(x) = A*cos(c + x)
Where A is the amplitude.
To find the amplitude of a cosine function, we just need to find half of the difference between the maximum and minimum value of the function:
By looking at the given graph, we can see that the maximum is y = 3, and the minimum is y = -3
Then the amplitude is:
A = (3 - (-3))/2 = 6/2 = 3
The correct option is B.
If you want to learn more, you can read:
Answer: It’s 4 they’re all wrong (pretty sure I have the same graph)
Step-by-step explanation:
After rearranging the given formula to put b on one side, we found the reciprocal of b to be 1/b = 2y/(y-2x). Multiplying by 2 gives 2/b = 4y/(y-2x) in terms of x and y.
To find an expression for 2/b in terms of x and y, let's first rearrange the question's provided formula, b = 1/2x - 1/y, to express b on one side of the equation. This rearrangement allows us to then find the reciprocal of b, which is 1/b. Following that, we can multiply 1/b by 2 in order to give us the expression for 2/b.
With our initial formula, b = 1/2x - 1/y, if we multiply each term by 2y, the formula then becomes 2yb = y - 2x. Rearranging this formula gives us b = (y-2x)/2y. Once we have our rearranged formula, we can find the reciprocal of b, which is 1/b. Therefore, 1/b = 2y/(y-2x).
Finally, to find our desired expression, the expression of 2/b in terms of x and y, we multiply our expression of 1/b by 2, resulting in: 2/b = 4y/(y-2x).
#SPJ12